Study of Venturi tube geometry on the hydrodynamic cavitation for the generation of microbubbles - Li, Mingda; Bussonnière, Adrien; Bronson, Matthew; Xu, Zhenghe; Liu, Qingxia (Minerals engineering, 2019)
•Effects of Venturi geometries on cavitation was studied by experiment and simulation.•Hydrodynamic cavitation increases flow resistance.•Small outlet angle is favorable for hydrodynamic cavitation to generate microbubbles.•The amount of microbubble generation increases with dissolved air in water. Venturi tubes have been extensively used to generate microbubbles through hydrodynamic cavitation. Due to their simple and flexible design, Venturi tubes have been used in a wide range of applications including mineral flotation. Although the impacts of the geometries of Venturi tubes on hydrodynamic cavitation have been studied in different specific contexts, no clear relation between cavitation and geometry parameters of Venturi tubes has been reported. In this work, we investigated numerically and experimentally the influence of several geometrical parameters on the cavitation inception detected by a hydrophone and the microbubble generation measured by a high-speed camera. Using a dimensionless number analysis, we found that the cavitation inception was determined by flow resistance, which significantly depends on the geometrical design of Venturi tube. In the cavitation regime, the flow resistance induced by cavitation increases linearly with reducing downstream cavitation number while the upstream cavitation number becomes constant regardless of the geometry of Venturi tube. A small outlet angle results in a low cavitation inception and a high microbubble production. Moreover, the degree of microbubble generation was found to increase with extra flow resistance and the dissolved gas concentration. The insights from this study provide a guideline for the design of efficient Venturi tubes for hydrodynamic cavitation system.